Hieratic texts from Tebtunis: including a survey of illustrated papyri - Kucharek, Andrea; Quack, Joachim Friedrich; Töpfer, Susanne (CNI publications / the Carsten Niebuhr Institute of Ancient Near East Studies, 2020)
This book contains a selection of hieratic texts from the ancient town of Tebtunis ? hymns and litanies, rituals of protection, a mythological narrative, scholarly compositions, and documentary texts ? as well as a survey of illustrated papyri.00Nearly all of the manuscripts are edited here for the first time, and many of the texts are hitherto unknown.00Kim Ryholt is professor of Egyptology in the Department of Cross-Cultural and Regional Studies, Carsten Niebuhr Department, at the University of Copenhagen
Keywords: Demotisch; Hieratisch; Papyrus; Funde; Tebtunis